Odpowiedź :
Cześć!
Szczegółowe wyjaśnienie:
[tex] \frac{2}{3} \cdot( - 12.3) \cdot( - \frac{5}{9} ) = \frac{2}{3} \cdot( - \frac{123}{10} ) \cdot( - \frac{5}{9} ) = \frac{41}{5} \cdot \frac{5}{9} = 41 \cdot \frac{1}{9} = \frac{41}{9} = \boxed{4 \frac{5}{9} }[/tex]
Odpowiedź:
2/3 *(-12,3) *( -5/9)= 2/3 *(- 12 i 3/10) *(-5/9)= 2/3 *(- 123/10 *(-5/9)( skracamy
10 i 5 przez 5, oraz 123 i 9 przez 3)=2/3 *(-41/2)*(-1/3)( skracamy
2 i 2 przez 2)= 1/3 *(-41) *(-1/3)= -41/3 *(-1/3)= 41/9= 4 i 5/9
Szczegółowe wyjaśnienie:
Zamieniamy liczby dziesiętne na ułamki zwykłe i mnożymy.